RETRACTED: Tax resident status: approaches to determination and consequences of its loss by an individual - Berman Alisa; Ershov Nikita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001